Pomiar subiektywnej jakości życia na poziomie lokalnym — studium przypadku - Rogala, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The paper concerns a project which was carried out in 2015. The main aim of the project was to develop a method, and then to measure the subjective quality of life of the inhabitants of 12 municipalities of the province of Lower Silesia. The questionnaires provided responses from 671 respondents who rated their satisfaction with life and the importance and satisfaction with various components of quality of life. On this basis the possibility of using measurement of subjective quality of life in the creation and evaluation of local and regional development programs was specified
Keywords: subiektywna jakość życia; ocena jakości życia; rozwój lokalny i regionalny